الاختيارات الفقهية لمحمد بن عبد السلام الهواري من خلال كتابه تنبيه الطالب لفهم ألفاظ جامع الأمهات لابن الحاجب - وهيبة بن فريحة; د/الأزهاري دمانة (جامعة عمار ثليجي الاغواط, 2023)
تناولت في هذه المذكرة الاختيا ا رت الفقهية لأحد أعلام الماليية، الإمام محمد بن عبىد السىلام الهىىواري، وذلىىك مىىن خىىلال كتابىىه "تنبيىىه الطالىىب" والىىذي ،عىىد واحىىدا مىىن أدم الشىىروح علىىى جىىامع الأمهىىات لابىىن الحاجىىب، مقتصىىرة فىىي ذلىىك علىىى بىىاب الصىىلاة، بهىىدف التعريىىب بشىىخص الإمىىام وتقريب بعض فقهه لطلاب العلم ، وإث ا ري فقه الخىلاف مىن خىلال أدلىة اختيا ا رتىه الفقهيىة، حيىث إن ا لاختيىىىار الفقهىىىي بضىىىوابطه وشىىىروطه ،سىىىاهم فىىىي تفعيىىىل حركىىىة الاجتهىىىاد ونبىىىذ التقليىىىد والتعصىىىب المذهبي، ويبرز خلاصة ما توصل إليه الإمام في المسا ل الخلافية بعد تقصي الأدلة. Abstract In this dissertation, I have examined the juristic choices of one of the leading scholars of the Maliki school, Imam Muhammad Ibn Abdul-Salam Al-Huwari, through his book "Tanbih Al-Talib". The book is considered one of the most precise commentaries on Ibn Al-Hajib's "Jami' Al-Ummahat". The focus of my study was on the chapter of prayer, with the aim of introducing the Imam's personality and life, providing some of his jurisprudence to students of knowledge, and enriching the jurisprudence of disagreement through the evidence of his jurisprudential choices. The jurisprudential choice, with its criteria and conditions, contributes to activating the movement of ijtihad and rejecting blind imitation and sectarianism. The dissertation highlights the Imam's conclusions on controversial issues after scrutinizing the evidence